2022
DOI: 10.1055/a-1948-2779
|View full text |Cite
|
Sign up to set email alerts
|

Labor Induction Outcomes with Outpatient Misoprostol for Cervical Ripening among Low-Risk Women

Abstract: Objective: In 2012, two Kaiser Permanente Northern California hospitals began offering outpatient cervical ripening with oral misoprostol under a study protocol. We evaluated inpatient time from admission to delivery and adverse maternal and neonatal outcomes associated with outpatient use of misoprostol for cervical ripening among low-risk women with term pregnancies. Study Design: We conducted a retrospective cohort study of 345 women who received misoprostol outpatient vs. inpatient at the study sites (n=1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Our results are consistent with two available studies using single doses of misoprostol for outpatient cervical ripening. Kandahari et al conducted a retrospective cohort study of 345 women undergoing cervical ripening as an outpatient regimen 17 . Roloff et al conducted a retrospective cohort study comparing 56 women induced as outpatients with matching controls induced as inpatients 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with two available studies using single doses of misoprostol for outpatient cervical ripening. Kandahari et al conducted a retrospective cohort study of 345 women undergoing cervical ripening as an outpatient regimen 17 . Roloff et al conducted a retrospective cohort study comparing 56 women induced as outpatients with matching controls induced as inpatients 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Kandahari et al conducted a retrospective cohort study of 345 women undergoing cervical ripening as an outpatient regimen. 17 Roloff et al conducted a retrospective cohort study comparing 56 women induced as outpatients with matching controls induced as inpatients. 18 Both studies showed shorter time from admission to delivery with outpatient start of induction and no significant differences in delivery outcomes compared with an inpatient group.…”
Section: Discussionmentioning
confidence: 99%